2013
DOI: 10.1097/pcc.0b013e31828a746c
|View full text |Cite
|
Sign up to set email alerts
|

Are Pediatric Critical Care Medicine Fellowships Teaching and Evaluating Communication and Professionalism?*

Abstract: Objective To describe the teaching and evaluation modalities utilized by pediatric critical care medicine (PCCM) training programs in the areas of professionalism and communication. Design Cross sectional national survey. Setting PCCM fellowship programs. Subjects PCCM program directors. Interventions None. Measurements and Main Results Survey response rate was 67% of program directors in the United States, representing educators for 73% of current PCCM fellows. Respondents had a median of 4 years ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 38 publications
(21 reference statements)
2
18
0
Order By: Relevance
“…While fellows perceive that many faculty do not intentionally teach by role modeling, prior data would suggest that faculty view this technique as a crucial technique 9 . Of note, over half of fellows reported that faculty role modeling behaviors observed were “mostly positive with some negative behaviors.” While observed role modeling behaviors are more often positive, fellows reported that faculty behaviors were negative as often as they were positive for both communication (25%) and professionalism (21%).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…While fellows perceive that many faculty do not intentionally teach by role modeling, prior data would suggest that faculty view this technique as a crucial technique 9 . Of note, over half of fellows reported that faculty role modeling behaviors observed were “mostly positive with some negative behaviors.” While observed role modeling behaviors are more often positive, fellows reported that faculty behaviors were negative as often as they were positive for both communication (25%) and professionalism (21%).…”
Section: Resultsmentioning
confidence: 99%
“…Investigators, developed a 29 question survey using the modified Delphi technique to be administered to PCCM fellows. This questionnaire was adapted from a previously conducted survey of PCCM fellowship program directors which was based on ACGME and American Board of Pediatrics requirements for teaching of communication and professionalism 4, 9, 13 . The final survey included 11 questions regarding specific elements of teaching and evaluating communication, 11 addressing elements of teaching and evaluating professionalism, 5 demographic questions and 2 qualitative questions concerning perceptions of teaching and evaluating communication and professionalism.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations